Generalized Lindelöf Finiteness Conditions for the λ-Type of a Subharmonic Function - Kondratyuk, Ya. V.; Kondratyuk, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We establish a finiteness criterion for the λ-type of a subharmonic function. In the case where λ(r) = r ρ L(r), ρ, where L is a slowly varying function, this criterion coincides with the Lindelöf criterion.